Penerapan Analisis Keberlanjutan Terhadap Permakultur di Kebun Hanif, Padalarang, Jawa Barat - Ardely, Michelle; Yudha, Eka Purna (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2026)
Indonesia holds significant potential in sustainable organic agriculture. However, prevalent consumptive behavior leads to high food waste, causing multidimensional impacts on environmental, social, and economic aspects. To address these challenges, this study aims to describe the application of permaculture ethics and its impact on sustainability at Kebun Hanif, concurrently analyzing the permaculture sustainability status across its social, environmental, and economic dimensions. This research employed a qualitative approach, focusing on in-depth interviews. Data obtained were analyzed using the MDS-RAPS method, complemented by Leverage analysis and Monte Carlo simulation to assess the sustainability status across the three dimensions. Analysis results indicate that permaculture at Kebun Hanif is highly sustainable in both economic and environmental dimensions. Meanwhile, in the social dimension, its sustainability level is classified as moderately sustainable. The permaculture implemented at Kebun Hanif provides valuable guidance to encourage broader permaculture adoption and support optimal sustainability enhancement.